2021
DOI: 10.3390/biology10101027
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Gut Microbiota Composition in the Pathophysiology of Gestational Diabetes Mellitus: A Systematic Review

Abstract: General gut microbial dysbiosis in diabetes mellitus, including gestational diabetes mellitus (GDM), has been reported in a large body of literature. However, evidence investigating the association between specific taxonomic classes and GDM is lacking. Thus, we performed a systematic review of peer-reviewed observational studies and trials conducted among women with GDM within the last ten years using standard methodology. The National Institutes of Health (NIH) quality assessment tools were used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Another inconsistency could be the close similarity between gout metagenomes to autoimmune instead of metabolic diseases like T2D. Despite systemic inflammation and urate degradation as presumptive non-invasive diagnostic markers induced by dysbiosis, T2D-like dysbiosis is not similar to arthritis diseases like gout (Kunasegaran et al 2021 ). The studies on microbiome of diabetic foot ulcers (DFU) do not seem to produce great evidence based medicine (Schmidt 2021 ).…”
Section: Gut Bacteriome Alterations and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another inconsistency could be the close similarity between gout metagenomes to autoimmune instead of metabolic diseases like T2D. Despite systemic inflammation and urate degradation as presumptive non-invasive diagnostic markers induced by dysbiosis, T2D-like dysbiosis is not similar to arthritis diseases like gout (Kunasegaran et al 2021 ). The studies on microbiome of diabetic foot ulcers (DFU) do not seem to produce great evidence based medicine (Schmidt 2021 ).…”
Section: Gut Bacteriome Alterations and Diabetesmentioning
confidence: 99%
“…Since these studies with evidence based medicine as to gut microbiota and GDM are up to date, it is high time for clinicians to incorporate personalized medicine targeting microbiota modulation. This can be done through dietary intervention (Kunasegaran et al 2021 ). However, western diets are metabolically less stable and when not monitored, might lead to complications like diabetes and obesity (Higgins et al 2021 ).…”
Section: Prospective Study Designsmentioning
confidence: 99%
“…A key indicator of a healthy gut microbiota health is its composition, which remains fairly stable over long periods even under short-term perturbations [122] . Alterations in the human gut microbiota are collectively referred to as dysbiosis and can be typically linked to certain health conditions such as metabolic, gastrointestinal, and mental disorders [123] , [124] , [125] . A recent study illustrated the predictive power of GSMMs and CBM methods for probing the metabolic behavior of the microbiota of healthy and Parkinson's disease patients [31] .…”
Section: Genome-scale Stoichiometric Models Of Metabolismmentioning
confidence: 99%
“…Synbiotics are regarded as indigestible food, which could stimulate and activate bacteria in the digestive tract [ 19 ]. It has shown that probiotic/synbiotic supplements are beneficial for pregnancy, which could alleviate insulin resistance and improve lipid metabolism [ 20 ]. However, the effect of probiotic/synbiotic supplementation on GDM is controversial, as some randomized controlled trials (RCTs) reported significant improvement in blood glucose control while there was no difference after intervention in other studies [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%